Natural vaporization system of seawater using plastic plate - Chung, Lee Ping (School of Materials Engineering, University Malaysia Perlis, 2010)
This report discussed about natural vaporization system of seawater using plastic plate. This experiment is based on the idea that every kind of water can be turn into water droplet using the concept of vaporization. Undrinkable seawater is used to turn into drinking water that can be used directly by human being in the critical area such as refugee camp and desolate place. In this experiment, seawater was being used for natural vaporization concept under the solar energy. In this study, seawater and diamond shape box is used for natural vaporization concept. SolidWorks is used for diamond shape box drawing. After the vaporization process, the collected amount sample is filtered with filter paper and filter funnel. Besides that, the quantities of water droplets by using measuring cylinder are being measured to all samples. Then, the scientific analyses of pH, hardness test were conducted at the lab. Based on the analysis data, shown that the value of pH, calcium and magnesium hardness are same at the level of drinking water. As a conclusion, prove that undrinkable seawater can be turn into drinking water after vaporization process.